Die effek van SHIP® (spontaneheling intrasistemiese proses) by adolessente tennisspelers (Afrikaans) - Steyn, Barend Johannes Marthinus (University of Pretoria, 2013)
Thesis (DPhil)--University of Pretoria, 2009.